Predicting non-small cell lung cancer prognosis by fully automated microscopic pathology image features - Kun-Hsing Yu (Nature Portfolio, 2016)
Diagnosis of lung cancer through manual histopathology evaluation is insufficient to predict patient survival. Here, the authors use computerized image processing to identify diagnostically relevant image features and use these features to distinguish lung cancer patients with different prognoses.